Laboulbeniomycetes (Fungi, Ascomycota) of Denmark - Santamaria, Sergi; Pedersen, Jan (European Journal of Taxonomy, 2021)
In this study, the thallus-forming Laboulbeniomycetes (Herpomycetales and Laboulbeniales) from Denmark are presented as an illustrated monograph. Sixteen species and one genus are newly described based on morphology and ecology (host association). The new genus is named Tanmaurkiella Santam. gen. nov. and includes two species: T. pselaphi Santam. gen. et sp. nov. (type species) and T. huggertii Santam. gen. et sp. nov., both on Pselaphus heisei Herbst, 1792 (Col. Staphylinidae Pselaphinae). The other 14 new species are Amorphomyces ventricosus Santam. sp. nov. on Myrmecocephalus concinnus (Erichson, 1839) (Col. Staphylinidae Aleocharinae), Cantharomyces papillatus Santam. sp. nov. on Bledius terebrans (Schiødte, 1866) (Col. Staphylinidae Oxytelinae), Cryptandromyces cryptophagi Santam. sp. nov. on Cryptophagus distinguendus Sturm, 1845 (Col. Cryptophagidae), Cryptandromyces danicus Santam. sp. nov. on Euconnus wetterhallii (Gyllenhal, 1813) (Col. Staphylinidae Scydmaeninae), Dimeromyces oculatus Santam. sp. nov. on Longitarsus luridus (Scopoli, 1763) (Col. Chrysomelidae), Euphoriomyces enghoffii Santam. sp. nov. on Leiodes rugosa Stephens, 1829 (Col. Leiodidae), Euphoriomyces smicri Santam. sp. nov. on Smicrus filicornis (Fairmaire & Laboulbène, 1855) (Col. Ptiliidae), Laboulbenia inexpectata Santam. sp. nov. on Acupalpus exiguus Dejean, 1829 (Col. Carabidae), Laboulbenia pygidicola Santam. sp. nov. on Syntomus truncatellus (Linnaeus, 1761) (Col. Carabidae), Monoicomyces brachiatus Santam. sp. nov. on Atheta sodalis (Erichson, 1837) and Ocyusa picina (Aubé, 1850) (Col. Staphylinidae Aleocharinae), Monoicomyces crassicaulis Santam. sp. nov. on Oxypoda elongatula Aubé, 1850 (Col. Staphylinidae Aleocharinae), Monoicomyces reboleirae Santam. sp. nov. on Gnypeta carbonaria (Mannerheim, 1830) (Col. Staphylinidae Aleocharinae), Monoicomyces validus Santam. sp. nov. on Atheta vestita (Gravenhorst, 1806), Aleochara grisea Kraatz, 1856, and Geostiba circellaris (Gravenhorst, 1806) (Col. Staphylinidae Aleocharinae), and Stigmatomyces thoracochaetae Santam. sp. nov. on Thoracochaeta brachystoma (Stenhammer, 1855) (Diptera Sphaeroceridae). The total number of laboulbeniaceous species from Denmark rises from 29 to 195, which means that 166 are here reported as new country records. Among these, Kainomyces isomali Thaxt. deserves special mention as it is a new European record. The same applies to nine species which are reported here for the first time after their original description. For this study, an intensive sampling programme has been realized, with 429 Danish localities screened including around 1900 collections with fungi. Two new synonymies are established: Laboulbenia acupalpi Speg. (Spegazzini 1915a) syn. nov. for Laboulbenia stenolophi Speg. (Spegazzini 1914), and Monoicomyces oxytelis Huldén (Huldén 1983) syn. nov. for Monoicomyces invisibilis Thaxt. (Thaxter 1900). The new combination Peyritschiella oxyteli (Cépède & F.Picard) Santam. comb. nov. is proposed for Rheophila oxyteli Cépède & F.Picard including neotypification, and delimitation of Peyritschiella protea Thaxt. is incorporated. Lectotypes for Laboulbenia polyphaga Thaxt. and Symplectromyces vulgaris (Thaxt.) Thaxt. are designated. Nineteen species are illustrated here with photographs for the first time. Three species: Eumonoicomyces papuanus Thaxt., Peyritschiella protea, and Stigmatomyces euconni F.Picard, which were reported from Denmark in the literature should be removed from the Danish Funga. We have examined the following types of Thaxter from FH (Farlow Herbarium, Harvard University Herbaria): Asaphomyces cholevae Thaxt., Dimorphomyces myrmedoniae Thaxt., Eumonoicomyces papuanus, Laboulbenia polyphaga, Peyritschiella protea, Rhadinomyces pallidus Thaxt., and Symplectromyces vulgaris. Ceratomyces pyrenaeus Santam. is newly recorded from USA, and this is also a new record from the American continent. Description of the genus Cryptandromyces Thaxt. has been emended to incorporate the new species here described. Morphology of the antheridium in Eumonoicomyces papuanus is studied, and the status of the genus Eumonoicomyces Thaxt. vis-à-vis Monoicomyces Thaxt. is discussed. Identification keys are provided for genera and species. In support of the additional aim of this work to serve as a reference for the study of Laboulbeniomycetes fungi in Europe, we include maps and the Appendix 1 for comparison of the known species in the ten most diverse, better studied, European countries.